Pedagogia do cuidado: a relação de saberes e valores no trabalho do programa saúde da família - Eliana Aparecida Villa (2008)
Marxist studies evidence work as essential to the existence and development of the human being. However it's remarkable that in the heath area the educational dimension of work as the experience of the human development is left beside. With the changes implemented in the Family Health Program, the work started to be done by teams, implying an approach between the conception and execution of work, in which workers are required to take part actively. Within this context, the main purpose of this study is to analyze the knowledge relation established among the members of family health teams at a Health Center in Belo Horizonte. It is a qualitative research, based on the Marxist reference framework, ergology and psychodynamics of work, as well as on studies about work in health. Through this analysis it was possible to reveal that the Family Health Program defines conditions and organization of the work in which, by one hand may be a source of suffering and frustration for the workers and, by the other, may be a potential pedagogical and therapeutic power, capable of producing knowledge and pleasure. For all workers, work is a source of learning; there is a pedagogy inscribed in the experience of care which is shown through: an individual and collective construction of knowledge among professionals; a more democratic relation, which loosens the knowledge- power network; a technical competence inserted in the worker's bodies which produces new skills; a therapeutic interaction mediated by language; a relation that could be called solidarity or compassion. Therefore, the care assumes the statute of a reconstructive category, which joins different kinds of knowledge and values, through the renormalization of the activity, which allows a renewal of senses for the work and the worker. Thus, we consider the influence of work in all aspects of life and rely on an approach that consider the subjective aspects of the worker, his knowledge and values, as fundamental elements of individual and collective reconstruction of/in work.